A53T alpha-syn regulates triacylglycerol content in dopaminergic neurons exposed to oxidative stress - Sánchez Campos, Sofía (2014)
Iron-induced oxidative stress and pathological α-synuclein (α-syn) aggregation contribute to the loss of dopaminergic neurons in Parkinson Disease (PD). In this work, we characterized the status of lipid metabolism in N27 dopaminergic neurons and in neurons stably expressing A53T α-syn (a dominant mutation found in familial early onset PD) exposed to iron-induced injury. N27 dopaminergic neurons incubated with iron for 24 hs (Fe, 1mM) displayed increased levels of reactive oxygen species (ROS), lipid peroxidation and elevated plasma membrane permeability. A different lipid acylation profile was observed in fatty acid prelabeled N27 neurons exposed to Fe. [3H] arachidonic acid (AA) uptake was increased in triacylglycerols (TAG) whereas the incorporation of [3H] oleic acid into TAG showed no changes. AA incorporation increased in phosphatidylcholine and diminished in phosphatidylserine and phosphatidylinositol. Coincidently, TAG content was 40 % higher in Fe-exposed neurons than in controls. The accumulation of TAG was also observed by the appearance of Nile red positive lipid bodies. On the contrary, A53T α-syn neurons exposed to iron-injury showed no increase in TAG levels and diminished ROS content. Our results suggest that TAG accumulation could be a mechanism for AA storage and that α-syn could act as an iron scavenger during oxidative stress in dopaminergic neurons.